The influence of digitalization on work and employment in the Banking Sector in South Africa - Naidoo, Angie (My University, 2021)
Digitalization, through the adoption of digital technologies, is changing banking practice in South Africa (SA) resulting in new ways of working which in turn requires new knowledge and skills. Designed as an exploratory study, this research, applied an occupational analysis process to explore the empirical cases of key banking occupations to examine the influence of digitalization on the nature of work and conditions of employment in SA. It interrogated if and how, work within occupations is changing or may change in the future because of, or in response to, digitalization, with a view to determining the nature and direction of skills change to better inform skills planning. The adoption of digital technologies by banks in SA, changes the setting or the context of occupations. To explore these occupational changes, five dimensions of occupations were examined, that is, jobs, work, knowledge, skills and employment. The results of this study provide an indication of occupations and jobs that are disappearing as well as those that are emerging; new tasks and responsibilities (changes to work); emerging generic and specialized knowledge and skills; changes to skills levels and changes brought about through the adoption of flexible work arrangements. Examining occupations in this way is useful for sector skills planning to inform occupational shortage sand the identification of current and future skills needs linked to digital transformation
A research report submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirement for the degree of Master of Education (MEd), 2021